Perception and practice of child labour among parents of school-aged children in Ibadan, southwest Nigeria (2009)
Background The problem of child labour has lingered on in many countries because of the complex combination of social, cultural and economic factors involved. Parents play a critical role in child labour as it provides much needed extra income for the family. This study was carried out among parents of school-aged children in an urban, low-income community to determine the factors associated with child labour and attitudes to child labour in the community. Methods A cross-sectional study was carried out in an urban community in Ibadan, southwest Nigeria. Questionnaires were administered to parents of school-aged children. Results A total of 473 parents were interviewed. They were aged between 23 and 56 years, mean 37.9 years. Thirty-nine per cent of parents indicated that they thought their school-aged children should work. More women than men, those from polygamous homes and those with lower educational status held this view. Reasons given for wanting their children to work were to supplement family income, 45%, to gain experience, 35% and to help in family business, 10%. In all, 236 (50%) respondents reported that their school-aged children were working. Parental factors associated with practice of child labour were polygamous marriage, low educational status, unskilled or partly skilled occupation and large family size. Seventeen per cent of parents with working children were not satisfied with their children’s work conditions and complained of low earnings, long working hours, work on school days and unsafe work environment. Measures suggested to control child labour include addressing the issue of household poverty, public enlightenment about the ills of child labour and free education up to junior secondary level. Enforcement of child labour laws was the least mentioned. Conclusion We conclude that control of child labour should be a multifaceted approach involving poverty alleviation, family planning to reduce family size and free, compulsory education up to junior secondary level. Public enlightenment especially for mothers will be of additional benefit.